2007
DOI: 10.1530/eje-06-0611
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone-binding protein is directly and IGFBP-3 is inversely associated with risk of female breast cancer

Abstract: Objective: Several components of the GH and IGF systems have been implicated in the development of malignancies. All components of these hormonal systems have never been jointly evaluated in female breast cancer, and previous studies have not examined the role of IGF-binding proteins (IGFBP-4, IGFBP-6) or GH-binding protein (GHBP). Design: Hospital-based case-control study. Methods: In this sample of primarily postmenopausal women, we obtained serum measures of IGF-I, IGF-II, and binding proteins IGFBP-1, IGFB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…The IGFBP6 gene codes for a protein that binds with high affinity to insulin-like growth factor-2 (IGF-II) (32), which plays a role in cellular proliferation, differentiation, and migration, and is regulated by the IGFBP6 protein (32). Expression of IGFBP6 may be associated with cancer incidence (32), with studies finding lower expression of the protein in the serum of breast cancer patients when compared to the serum of those with benign breast disease (33, 34). Our finding of hypermethylation of IGFBP6 in obese patients suggests that obesity may lead to reduced expression in breast tissue via gene methylation.…”
Section: Discussionmentioning
confidence: 99%
“…The IGFBP6 gene codes for a protein that binds with high affinity to insulin-like growth factor-2 (IGF-II) (32), which plays a role in cellular proliferation, differentiation, and migration, and is regulated by the IGFBP6 protein (32). Expression of IGFBP6 may be associated with cancer incidence (32), with studies finding lower expression of the protein in the serum of breast cancer patients when compared to the serum of those with benign breast disease (33, 34). Our finding of hypermethylation of IGFBP6 in obese patients suggests that obesity may lead to reduced expression in breast tissue via gene methylation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, elevated serum GH-binding protein (derived from the GHR by cleavage, and a measure of GHR expression [68]) is associated with a threefold increase in breast cancer incidence [69]. Immunohistochemical assessment has also revealed GHR overexpression in melanoma [70] and prostate carcinoma [71].…”
Section: Reviewmentioning
confidence: 99%
“…A similar result was observed for IGFBP1 in this study. The study of postmenopausal women showed an inverse association between IGFBP3 and risk of breast cancer, while other IGFBPs (IGFBP1, IGFBP4, and IGFBP6) were not significantly associated with breast cancer risk (39). There are also studies that reported no association between IGFBP3 and risk of cancer, or positive association between them (40,41).…”
Section: Introductionmentioning
confidence: 99%